Efektivitas Penerapan Pembelajaran Kooperatif Jigsaw untuk Meningkatkan Minat dan Hasil Belajar Siswa Kelas XI A6 di SMAN 2 Pamekasan - Zubier, Ach Faqih Jalil As; Zahroh, Latievatus; Ibana, Lukluk; Susanti, Trias Jaya; Chamroh, Siti (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the effectiveness of the implementation of the Jigsaw cooperative learning model in improving the interest and learning outcomes of class XI A6 students at SMAN 2 Pamekasan. The research method used is Classroom Action Research (CAR) which is carried out in two cycles. Data were collected through a learning interest questionnaire and learning outcome test. The data was analysed descriptively quantitatively. The results showed a significant increase in students' learning interest from an average of 78.45 (cycle I) to 85.31 (cycle II). Likewise, learning outcomes increased from an average of 75.5 with a completeness of 82.6% (cycle I) to an average of 87.8 with a completeness of 87.0% (cycle II). The implementation of the Jigsaw model has proven effective because students can work together, discuss, and share information between group members, so that learning becomes more interesting and participatory. Thus, the Jigsaw cooperative learning model is feasible to be implemented in Biology learning to improve students' interest and learning outcomes.